Condylar osteochondroma: Report of a case with literature review - Anita Singhal; Ramesh Venkatpathy; Parul Singhal (Wolters Kluwer Medknow Publications, 2013)
Osteochondroma is one of the most common benign tumors of the skeleton, but osteochondroma of the mandibular condyle is relatively rare and may cause signs and symptoms similar to those seen in patients with temporomandibular joint (TMJ) dysfunction. This article aims to describe a case of osteochondroma of the mandibular condyle in a 30-year-old male with complaints of facial asymmetry, crossbite to the contralateral side, changes in condylar morphology, and malocclusion. Generally, management of these lesions includes total condylectomy or local resection. Conservative condylectomy with reshaping of the remaining condylar neck and repositioning of the articular disk was performed on the patient who is presently on routine follow-ups.